2008
DOI: 10.1136/sti.2007.027326
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection among people attending the voluntary counselling and testing centre and anti-retroviral therapy clinic of St Paul's General Specialised Hospital, Addis Ababa, Ethiopia

Abstract: This study shows a high prevalence and similar distribution of HBV infection in HIV-positive and HIV-negative people. However, with the emphasis given to HIV-positive cases, screening for HBV infection is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
28
11
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 24 publications
17
28
11
1
Order By: Relevance
“…Studying patterns of co-infection with HBV, HCV and HIV is of great importance, particularly in the context of controlling morbidity and mortality caused by liver disease. This study observed a lower HBV/HIV dual infection as compared to studies done in Kenya, Nigeria, Ethiopia and South Africa [23, 24,25,10, 26]. We also observed that the odds of being infected with HBV were twofold when one was HIV positive.…”
Section: Discussionsupporting
confidence: 68%
“…Studying patterns of co-infection with HBV, HCV and HIV is of great importance, particularly in the context of controlling morbidity and mortality caused by liver disease. This study observed a lower HBV/HIV dual infection as compared to studies done in Kenya, Nigeria, Ethiopia and South Africa [23, 24,25,10, 26]. We also observed that the odds of being infected with HBV were twofold when one was HIV positive.…”
Section: Discussionsupporting
confidence: 68%
“…These findings showed that that the vast majority of patients with diabetes have no increased susceptibility to infection by HBV than the general population. This study also showed that the study area to be of intermediate endemicity (2-8%) with HBV and consistent with previous serologic data from most region of Ethiopia [5, 810]. …”
Section: Discussionsupporting
confidence: 92%
“…Studies done in Ethiopian on different target population, for example a study done by Abebe et al (2003) [5] in Addis Ababa residents, Shimelis et al (2007) [8] at Saint Paul’‘s General Specialized Hospital on VCT clients, by Tessema et al (2010) [9] at University of Gondar on blood bank and by Negero et al (2011) [10] among VCT clients at Shashemene Hospital showed 7%, 5.7%, 4.7% and 5.7% HBsAg prevalence, respectively. When we compared these finding with ours, they showed intermediate endemicity prevalence like the current study but slightly higher.…”
Section: Discussionmentioning
confidence: 99%
“…The observed 4.7% HIV-HBV co-infection rate was lower compared with the study in North West Ethiopia which reported 5.6% [12]. Conversely, HIV-HBV co-infection rate of this study was higher as compared to worldwide HBV prevalence which was 3.1% [21] [22,23], both from Addis Ababa and lower than study in Kenya (6%) and Nigeria (6%) [19,24]. The reason for such variations in co-infection rate among HIV infected patients could possibly be due to difference in the distribution of these viruses in the various geographic locations, recruitment setting, sample size and ethnic variation.…”
Section: Discussioncontrasting
confidence: 53%